Hungary : 2013 Article IV Consultation and Third Post Program Monitoring Discussions-Staff Report; Informational Annex; Public Information Notice; and Statement by the Executive Director. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2013)
This paper presents 2013 Article IV Consultation and Third Post Program Monitoring discussions on Hungry. While the output gap remains sizable, inflation expectations are not well anchored, and after seven consecutive policy rate cuts a pause seems prudent. Further monetary policy easing can be supported by stronger macroeconomic policies. Some efforts have been made to improve labor participation, but potential growth remains far too low for a country that should converge faster to EU-average incomes. The IMF report suggests that maintaining market confidence and reviving growth are the most pressing priorities for which decisive action to improve policies is needed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet